Risiko Kesehatan pada Pemulung di TPA Air Dingin Kota Padang - Rahmi Hidayanti; Afridon Afridon; Aidil Onasis; Erdi Nur (Jurnal Kesehatan Manarang, 2022)
Scavengers live by collecting garbage, used items that can be recycled. Collecting garbage is one of the jobs that have health and safety risks and problems such as complaints of itchy skin, redness and burning. Scavengers working at the TPA Air Dingin were found not using personal protective equipment (APD) when working. This study aims to determine the factors that cause complaints of skin disorders in scavengers. The cross sectional research design is located at the TPA Air Dingin Padang City in 2021. The population is all scavengers who work at the TPA Air Dingin. The sample is a scavenger selected by the Simple Random method. Sampling (SRS). The number of samples is 91 respondents. data collection through interviews using a questionnaire. Data were analyzed using chi aquare statistical test for bivariate analysis and logistic regression for multivariate analysis. The results of the analysis of age, length of work, years of service,’personal hygiene and personal protective equipment’were associated’with complaints of skin disorders’(p value < 0.005). Dominant factors affecting complaints of skin disorders are age and years of service. It is recommended that scavengers use personal protective equipment ( APD) that functions properly to avoid complaints of skin disorders. Supervision and policies from relevant agencies regarding the importance of using personal protective equipment ( APD) for scavengers. In addition, it is necessary to conduct outreach activities to scavengers about the importance of personal hygiene and the use of personal protective equipment (APD).